Functional genomics gives new insights into the ectomycorrhizal degradation of chitin. Issue 2 (20th February 2023) - Maillard, François; Kohler, Annegret; Morin, Emmanuelle; Hossann, Christian; Miyauchi, Shingo; Ziegler‐Devin, Isabelle; Gérant, Dominique; Angeli, Nicolas; Lipzen, Anna; Keymanesh, Keykhosrow; Johnson, Jenifer; Barry, Kerrie; et al.
Summary: Ectomycorrhizal (EcM) fungi play a crucial role in the mineral nitrogen (N) nutrition of their host trees. While it has been proposed that several EcM species also mobilize organic N, studies reporting the EcM ability to degrade N‐containing polymers, such as chitin, remain scarce. Here, we assessed the capacity of a representative collection of 16 EcM species to acquire 15 N from 15 N‐chitin. In addition, we combined genomics and transcriptomics to identify pathways involved in exogenous chitin degradation between these fungal strains. Boletus edulis, Imleria badia, Suillus luteus, and Hebeloma cylindrosporum efficiently mobilized N from exogenous chitin. EcM genomes primarily contained genes encoding for the direct hydrolysis of chitin. Further, we found a significant relationship between the capacity of EcM fungi to assimilate organic N from chitin and their genomic and transcriptomic potentials for chitin degradation. These findings demonstrate that certain EcM fungal species depolymerize chitin using hydrolytic mechanisms and that endochitinases, but not exochitinases, represent the enzymatic bottleneck of chitin degradation. Finally, this study shows that the degradation of exogenous chitin by EcM fungi might be a key functional trait of nutrient cycling in forests dominated by EcM fungi.